2004
DOI: 10.1016/j.icvts.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumothorax: are we missing something?

Abstract: Most thoracic surgeons overlook the fact that spontaneous pneumothorax is one of the pulmonary complications of connective tissue disorders such as Marfan or Ehlers-Danlos syndromes, and they consider it as primary. In the following report we describe a unique case of spontaneous rupture of the sigmoid secondary to a spontaneous recurrent contralateral pneumothorax in a young patient with undiagnosed Marfan syndrome. The aim of this presentation is to raise a high index of suspicion of every thoracic surgeon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Th ese fi ndings of a strong association between PSP and MVP suggest that, in many patients, PSP may be the manifestation of a systemic abnormality of the connective tissue. Microscopically abnormal collagen fi bers and connective tissue of decreased tensile strength have been found in the lung tissue of PSP subjects, and pneumothorax has been suggested to the result of a forme fruste of Marfan syndrome in some cases, whereas MVP might be a further manifestation of a generalized connective tissue abnormality [16,17]. Bitar et al reported a prevalence of 38% for MVP in patients with PSP, compared to only 8% in age-matched controls [11].…”
Section: Resultsmentioning
confidence: 99%
“…Th ese fi ndings of a strong association between PSP and MVP suggest that, in many patients, PSP may be the manifestation of a systemic abnormality of the connective tissue. Microscopically abnormal collagen fi bers and connective tissue of decreased tensile strength have been found in the lung tissue of PSP subjects, and pneumothorax has been suggested to the result of a forme fruste of Marfan syndrome in some cases, whereas MVP might be a further manifestation of a generalized connective tissue abnormality [16,17]. Bitar et al reported a prevalence of 38% for MVP in patients with PSP, compared to only 8% in age-matched controls [11].…”
Section: Resultsmentioning
confidence: 99%
“…The lung connective tissue and the visceral and parietal pleura (including the blood and lymphatic vessels) are derived from the surrounding splanchnic mesenchyme ( i.e ., from the mesoderm). Thus, it is not surprising that the pathophysiology of PSP is coupled with inflammatory changes of the lungs and pleural cavity [24]. This structural/functional communication between the tissues of the pleura and lungs (based on the common embryonic origin of their connective tissue) is also expected to be reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of pneumothorax includes observation, needle aspiration, insertion of an intercostal tube drainage or invasive thoracoscopy or thoracotomy with pleuodesis or pleurectomy. 6 Video-assisted thoracoscopic surgery is an effective and safe treatment for children with spontaneous pneumothorax. [7][8][9] Although there are no specific pediatric guidelines for spontaneous pneumothorax, as proposed by O'Lone and colleagues in the larger pediatric case-series to date, indication for invasive surgical procedure should be advanced promptly (within 48 hours) for recurrence of pneumothorax and within 5 days for persistent pneumothorax.…”
Section: Discussionmentioning
confidence: 99%